Emulsion stability and CO2 removal performance of MDEA-AMP blends with tween-80 surfactants - Siti Balqis Mohd Najib,; Mohd Nazri Mohd Sokri,; Mohamed Rashid,; Norhana Mohamed Rashid,; Tan, Adeline Zhi Li; Sri Ghanesh Muniandy, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Carbon dioxide (CO2) is a corrosive and inflammable gas found in natural gas. The most widely technique used for CO2 separation in the natural gas industry is via amine absorption method. However, due to the corrosive nature of amines, researchers actively looking for an alternative method to separate CO2. Therefore, the emulsion liquid membrane (ELM) was developed to address this issue. In spite of that, it still remains as challenge to find suitable formulation to produce stable emulsion with good CO2 removal performance. In this study, the amine blend emulsion containing Methyldiethanolamine (MDEA) and 2-amino-2-methyl-1-propanol (AMP) with Tween-80 (Polysorbate-80) were prepared. An aqueous phase was formed by blending of MDEA and AMP in sodium hydroxide (NaOH) solution. The organic phase composed of kerosene and Tween-80 used as surfactant. The effect of varying concentrations of Tween-80 on the emulsion stability and CO2 absorption capacity of ELM were investigated in this study. The emulsion was prepared by mixing the aqueous and organic phases for 5 minutes at a speed of 10,000 rpm until it become homogenous. The CO2 absorption capacity was conducted in a rotating disc contactor column with a 2-bar pressure of CO2 gas supply. This study demonstrated that, by blending of 8% v/v MDEA and 4% v/v AMP with 10% v/v Tween-80, 56.89% of CO2 removal could be achieved while maint aining an emulsion stability of 95%